Reactivity of 5‐(Alkynyl)dibenzothiophenium Salts: Synthesis of Diynes, Vinyl Sulfones, and Phenanthrenes. Issue 29 (5th May 2021) - Kafuta, Kevin; Rugen, Christian J.; Heilmann, Tobias; Liu, Tianshu; Golz, Christopher; Alcarazo, Manuel
Abstract: The reactivity of 5‐(alkynyl)dibenzothiophenium salts 1 is explored in the presence of different nucleophiles, dienes, and under photochemical conditions. Reaction with lithium acetylides affords diynes in moderate yields; while depending on the substitution pattern, the reaction with sulfinates delivers either the alkyne transfer products, alkynyl sulfones, or β‐(sulfonium) vinyl sulfones through addition to the C−C triple bond. Similar behavior is observed when tosylamines are used as nucleophiles. Salts of general formula 1 also react with dienes to render the corresponding Diels‐Alder cycloadducts. The vinyl sulfonium salts obtained by these routes further react with nucleophiles through a Michael addition, dibenzothiophene elimination sequence. Alternatively, they also engage in photoinduced radical cyclizations to produce substituted phenanthrenes. Attempts to use this specific addition/radical cyclization sequence for the construction of the 6 a, 7‐dehydroaporphine skeleton present in several families of alkaloids are also described. Abstract : The synthetic potential of 5‐(alkynyl)benzothiophenium salts is further evaluated. In addition to their reactivity as electrophilic alkynylation reagents, they undergo regioselective additions to the C−C triple bond. The products thus obtained can be used for the synthesis of Z ‐vinyl sulfones and 9, 10‐substituted phenanthrenes.